Synthesis and Evaluation of Antioxidant and Cytotoxicity of the N-Mannich Base of Berberine Bearing Benzothiazole Moieties - Mistry, Bhupendra M.; Shin, Han-Seung; Keum, Young-Soo; Pandurangan, Muthuraman; Kim, Doo H.; Moon, So Hyun; Kadam, Avinash A.; Shinde, Surendra K.; Patel, Rahul V. (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Berberine, a quaternary ammonium salt from the protoberberine group of benzylisoquinoline alkaloids has drawn high attention for its several biological potencies. Objective: To furnish new rationalized derivatives based on berberine core which can deliver promising antioxidant and cytotoxic activities. Method: The N-Mannich base of an isoquinoline alkaloid, berberine, bearing substituted benzothiazole moieties was obtained. Novel synthesized analogues were in vitro screened for antioxidant efficacy toward 2,2-diphenyl- 1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radicals and in vitro cytotoxicity towards cervical cancer cell lines (HeLa and CaSki), an ovarian cancer cell line (SK-OV-3) and human renal cancer cell line (Caki-2). Cytotoxicity of the compounds toward normal cell lines was examined using the Madin-Darby canine kidney (MDCK) non-cancer cell line. Results: Analogues bearing a methoxy functional group (5e), acid functionality (5c), and a cyano group (5m) showed remarkable radical scavenging potential in DPPH and ABTS bioassays. Potent cytotoxicity exhibited by berberine against the HeLa cell line was attributable to the presence of a 2-aminobenzothaizole moiety (5a) and its 6-chloro congener (5g) on the berberine core, and the 6-cyano group (5m) on the benzothiazole ring revealed strong sensitivity for the CaSki cell line, whereas subjected scaffolds demonstrated diminished activity against the SK-OV-3 cell line. In addition, the compound with a 2-aminobenzothaizole moiety (5a), compound with methoxy functional group (5e) and compound with cyano group appeared with the most significant cytotoxicity effect in Caki-2 cell line. Their structures have been elucidated by FT-IR, 1H NMR, 13C NMR, and elemental analyses (CHN) essential research. Conclusion: N-Mannich bases of berberine were efficiently generated utilizing pharmacologically diverse substituted 2-aminobenzothiazole entities and final compounds were found remarkably active in antioxidant and cytotoxic assay. Hence, such types of compounds can be further studied or rationalized in future drug discovery studies.
Keywords: anticancer